Strategy in sponsorship - the basis for creativity - Whatling, Shaun (Henry Stewart Talks, 2008)
The difference between a strategy and a plan, Components and criteria of strategy, Clear objective setting as foundation, Parameters for creativity, Example of excellence in creative emerging from clear strategy
Archived at 2022/04/04